Letter: are opioid prescriptions associated with hepatic encephalopathy in patients with compensated cirrhosis? Authors' reply. Issue 7 (12th March 2020) - Moon, Andrew M.; Jiang, Yue; Rogal, Shari S.; Tapper, Elliot B.; Lieber, Sarah R.; Barritt, A. Sidney
Abstract : LINKED CONTENT This article is linked to Moon et al and Li et al papers. To view these articles, visit https://doi.org/10.1111/apt.15639 and https://doi.org/10.1111/apt.15661 .